The autonomist current in Brazil and the working class: Critical remarks on the revision of Marxism in the 1980s - Lovatto, Angélica (Pontifícia Universidade Católica de São Paulo, 2016)
In this article, the author analyzes the current autonomist movement that existed in Brazil throughout the 1980s, and aimed at revising Marxism, especially in the journal Desvios. This critical revision came about what, at the time, became known as the emergence of “new” social movements. Among the main participants of this current, the sociologist Eder Sader and the philosopher Marilena Chauí stood out, whose formulations, in the period, will be privileged here.